Rancang Bangun Drone Solar Cell untuk Pengintaian dalam Mendukung Operasi Keamanan Laut - Hartanto, Endin Tri; Sulistyo, Hari; Adi, Anang Prasetiya (Universitas Trunojoyo Madura, 2022)
The development of defense equipment and military technology in the TNI-AL is carried out in order to support the strengthening of the National Defense Strategic Industry (Instranas). Several steps have been taken in the development of defense equipment and military technology in the TNI-AL, namely by carrying out research and development of defense equipment. One of them is conducting research on unmanned aerial vehicles (UAV). The use and development of unmanned aircraft was initially carried out by the military to carry out military and intelligence operations. To carry out reconnaissance functions to support maritime security operations, requiring long endurance, a Solar Cell Drone is designed by utilizing solar energy. Based on the results of the design and testing that have been carried out, the drone is able to fly as long as it gets a supply of solar energy, which is throughout the day with the main load on the propulsion system. The thrust value obtained is 1266.8 watts or the equivalent of 3,998 kg of thrust which is able to fly a drone with a weight of 6.7 kg. The control system developed uses the Pixhawk 4 flight controller and remote control, the data communication system uses Telemetry NRF24L01 2.4 GHz. The results of this design and test can be a pioneer in developing Solar Cell Drones for the independence of the Indonesian Navy's defense equipment in the future.